Bioindicators of erosive dynamics in beach and dune systems in the portuguese mainland coast - Martins, Mónica C. (2015)
The litoral psammophilic ecosystems are organized according gradients leaning from the sea to interior areas, including a succession of phytosociological associations, correspondent to well discriminate biotopes, according their geomorphologic, soil and ecological characteristics. In the stable sandy shores (in terms of erosion balance), the different communities occupy relatively wide zonal tracks, with clear transitions. However, in situations of beach downwasting and coastline retreat, the mobile sands tend to advance inland, often compressing the zonal gradient, and distinct communities tend to overlap. Since the herbaceous hemicryptophitic flora typical from the beach and instable dunes has intrinsic colonization skills, high tolerance (or even preference) to burial, and elevated growing rates, it can quickly adapt to the instability of the topographic surface, accompanying its movement to the interior. Yet, the growing rates of the woody chamaephitic vegetation, characteristic of the more interior and relatively stable dune (gray dune) are slower, in addition to a lower capability to resist to burial. Thus, sea advance and inherent sands mobility inland, combined with the dissimilar resilience of plant associations, results in the in the overlap of the chamaephitic taxa and in the amalgamation of species from different communities. The main objective of this work was to study general trends of erosion along the Portuguese softline mainland coast, based in the analysis of the dominant associations that occur along the psammophilic gradient. It was focused in the role played by some plants has bioindicators of the velocity of erosional processes caused by wind transportation, sea dynamics and coastal retreat. Plants that can be used has reliable bioindicators are identified. Correlations between the observed alterations in the theoretical model of a coastal psammophilic gradient, and the intensity of erosion are established. The intensity of the phenomenon is analyzed and quantified along different sectors of the Portuguese coast.